2009
DOI: 10.1038/pcan.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective estrogen receptor modulators on cell proliferation and estrogen receptor activities in normal human prostate stromal and epithelial cells

Abstract: We examined the effect of E 2 and selective estrogen receptor modulators (SERMs) on the proliferation and estrogen receptor (ER) activities in normal human prostate cells. SERMs such as toremifene, raloxifene and tamoxifen suppressed the proliferation of prostate epithelial and stromal cells whereas anti-androgens did not. In prostate stromal cells, the transactivation activities of ER were enhanced by adding E 2 and reduced remarkably by toremifene. The results indicate that the ER-mediated pathway plays a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Based on the results of both MTT assay and FACS analysis, TAM exerted a much higher apoptotic activity compared to MIF. Very recently, it was reported that the ER-mediated pathway plays a central role in the growth of normal prostate cells [13]. This finding may support the high cytotoxicity of TAM against DU-145 cells found in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results of both MTT assay and FACS analysis, TAM exerted a much higher apoptotic activity compared to MIF. Very recently, it was reported that the ER-mediated pathway plays a central role in the growth of normal prostate cells [13]. This finding may support the high cytotoxicity of TAM against DU-145 cells found in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent reports have shown that TAM inhibits the proliferation and induces apoptosis not only in estrogen receptor (ER)-positive breast cancer cells, but also in ER-neg-ative breast cancer cells and other cancer cells; i.e., prostate cancer, ovarian cancer, colorectal cancer, and brain cancer [1,13,17]. Non-genomic effects of TAM has been suggested in many cell lines; including the inhibition of protein kinase C [3], interferences with the function of ion channels [7], and the activation of extracellular signal-regulated kinase (ERK1/2) [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, most men who take combination therapy do not get any added benefit while additional four out of hundred patients face the risk of becoming impotent [55]. In view of recent studies indicating the importance of ER-mediated pathways in the pathogenesis of BPH [56,57]; selective modulation of estrogen receptor action offers an alternative and promising approach for the management of prostate disease. The in vivo data of present study clearly indicates the potential of SERMs in regulating prostatic size, which could be amplified further by combined 5α-reductase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al observed that ERK was activated by E2, causing the proliferation of PrSC, 22 whereas Nomura et al showed that toremifene, an ERa antagonist, strongly suppressed the ER activity and proliferation of primary PrSC. 23 Primary cultures of normal human prostatic epithelial and stromal cells have been used as useful models for studying the pathogenesis of BPH experimentally. However, the limitations of the prostatic primary cultures should also be considered; their proliferation rate is slow and they have a limited lifespan in culture, eventually undergoing senescence.…”
Section: Era As a Promoting Factor Of Bphmentioning
confidence: 99%
“…84 From a chemopreventative point of view, a clinical trial was carried out that showed that toremifene decreased the incidence of prostate cancer development in men with HGPIN. 85 Toremifene also strongly suppresses ER activity and cell proliferation in PrSC, 23 and the ability of toremifene to decrease the incidence of prostate cancer might be attributed to the suppression of the stromal paracrine that stimulates the precancerous lesion. Experimentally, toremifene suppressed prostate cancer development in the transgenic adenocarcinoma of mouse prostate model, 86 and delayed tumor formation and prolonged survival compared with placebo-treated animals.…”
Section: Er As a Therapeutic And Chemopreventative Target Of Prostatimentioning
confidence: 99%